Screening and analysis of differentially expressed circRNAs and miRNAs in chronic diabetic extremity wounds - Li, Xiaoliang; Lv, Dan; Xie, Jiangfan; Ye, Xiangyang; Xia, Chengde; Liu, Dewu (Frontiers in Surgery, 2022)
Increasing evidence has shown that circular RNAs (circRNAs) and microRNAs (miRNAs) are involved in the development of endocrine and metabolic related diseases. However, there are few reports on the expression of circRNAs, miRNAs, and related co-expression and competitive endogenous RNA (ceRNA) in diabetic chronic refractory wounds. In this study, we compared the expression levels of circRNAs and miRNAs in diabetic chronic refractory wounds and normal skin tissues via high-throughput gene sequencing in order to identify differentially expressed circRNAs and miRNAs. Six abnormally expressed circRNAs and miRNAs were detected by reverse transcription qPCR to verify the results of RNA sequencing. The dysregulated genes were enriched and analyzed by gene ontology and the Kyoto Encyclopedia of genes and genomes was used to clarify their main functions. For significantly abnormal genes, a coding noncoding gene co-expression (CNC) network, and ceRNA network were constructed. CNC network analysis showed that hsa_circRNA_104175, hsa_ circRNA_ 001588, hsa_ circRNA_ 104330, hsa_ circRNA_ 100141, hsa_ circRNA_ 103107, and hsa_ circRNA_102044 may be involved in the regulation of chronic refractory wound healing processes in diabetes. This may be especially true in the regulation of vascular smooth muscle contraction related pathways and the actin cytoskeleton which affect the healing of chronic refractory wounds from diabetes. MiR-223-5p, miR-514a-3p, miR-205-5p, and miR-203a-3p, where each have a network targeting relationship with the above circRNAs, regulate the metabolism of nitrogen compounds in wound tissue by regulating NOD-like receptor signaling pathways, signaling pathways regulating pluripotency of stem cells, microRNAs in cancer, and ECM-receptor interaction. This study indicates that circRNAs, miRNAs, and their networks are associated with the development of chronic refractory wounds in diabetes mellitus and our research identifies new molecular biomarkers and targets for gene therapy.